Fabrication of periodic arrays of metallic nanoparticles by block copolymer templates on HfO2 substrates. (7th May 2015) - Frascaroli, Jacopo; Seguini, Gabriele; Spiga, Sabina; Perego, Michele; Boarino, Luca
Abstrect: Block copolymer-based templates can be exploited for the fabrication of ordered arrays of metal nanoparticles (NPs) with a diameter down to a few nanometers. In order to develop this technique on metal oxide substrates, we studied the self-assembly of polymeric templates directly on the HfO2 surface. Using a random copolymer neutralization layer, we obtained an effective HfO2 surface neutralization, while the effects of surface cleaning and annealing temperature were carefully examined. Varying the block copolymer molecular weight, we produced regular nanoporous templates with feature size variable between 10 and 30 nm and a density up to 1.5 × 10 11 cm −2 . With the adoption of a pattern transfer process, we produced ordered arrays of Pt and Pt/Ti NPs with diameters of 12, 21 and 29 nm and a constant size dispersion ( σ ) of 2.5 nm. For the smallest template adopted, the NP diameter is significantly lower than the original template dimension. In this specific configuration, the granularity of the deposited film probably influences the pattern transfer process and very small NPs of 12 nm were achieved without a significant broadening of the size distribution.